2013
DOI: 10.1177/1477370813500885
|View full text |Cite
|
Sign up to set email alerts
|

Wider and deeper: The future of criminology in Europe

Abstract: The European Journal of Criminology was launched 10 years ago. In this article, the journal's founding editor, David J. Smith, reflects on the journal's contribution to European criminology. The article recalls the ambitions for the journal when the idea was first discussed, and looks back over the first nine volumes to assess the extent to which these ambitions have been fulfilled. It argues that the study of crime must draw on both humanist and scientific traditions. Because its moral and political dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Following up on the results of this study and those of similar studies (e.g., Cohn and Iratzoqui, 2015;Farrington et al, 2019;Smith, 2014), we have identified five avenues for future research. First, it could be interesting to look into the topics addressed at the annual conferences of the American Society of Criminology, the British Society of Criminology, the Australian and New Zealand (ANZAC) Society of Criminology, and the Asian Criminological Society, and examine their state of affairs.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Following up on the results of this study and those of similar studies (e.g., Cohn and Iratzoqui, 2015;Farrington et al, 2019;Smith, 2014), we have identified five avenues for future research. First, it could be interesting to look into the topics addressed at the annual conferences of the American Society of Criminology, the British Society of Criminology, the Australian and New Zealand (ANZAC) Society of Criminology, and the Asian Criminological Society, and examine their state of affairs.…”
Section: Discussionmentioning
confidence: 78%
“…The presence of a topic referring to the (qualitative) critical study of the reaction to crime in addition to a topic that represents (quantitative) self-report research could be indicative of the width of research approaches in European criminology and suggests the absence of a theoretical or methodological domination in European criminology. However, this width is not reflected in terms of the national scope of studies, despite what some may have suggested earlier (Baars-Schuyt, 2001;Smith, 2014). One of the most influential topics, UK-based research (topic 36), clearly represents a dominance of research specific to the UK and UK data.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations